Забезпечення захисту інформаційних ресурсів організації - Гапонюк, К. В. (ХНУРЕ, 2023)
One of the main aspects of security issues in the organization is considered. The threat of hacking due to lack of awareness of personnel in the field of information protection, which poses a privacy risk for the company to its employees, was analyzed